PENGELOMPOKAN DATA VAKSIN MENGGUNAKAN METODE K-MEANS PADA KANTOR PEMERINTAH DESA BENDUNGAN - siti azhar; Dodi Solihin; Tati Suprapti; Umi Hayati; Kaslani (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Corona virus or Covid-19 is the name of the virus set by the World Health Organization (WHO) on March 9, 2020 where this corona virus was first discovered in Wuhan China on December 1, 2019. Corona viruses are a large family or viruses that attack animals and humans. When attacks humans, it will cause death. To minimize the number of cases that continue to increase, a recommendation for vaccination is set that aims to increase the immune system.From the data obtained, the authors are interested in further research on vaccine data. In order to group vaccine data, at this stage the cluster center is randomly selected from a set of population data. Next, K-Means tests each cluster in the data population and marks the cluster to one of the cluster centers that have been determined from the distance between the clusters and each cluster center.The result of testing the Clustering K-Means method on grouping vaccine data resulted in the grouping of data being divided into 2 clusters where cluster two (1) got the most data compared to cluster one (0). From the determination of the cluster is determined based on the parameter K 2.